Health Care Reform and Social Movements in the United States - Hoffman, Beatrix (American Public Health Association, 2008)
Because of the importance of grassroots social movements, or “change from below,” in the history of US reform, the relationship between social movements and demands for universal health care is a critical one. National health reform campaigns in the 20th century were initiated and run by elites more concerned with defending against attacks from interest groups than with popular mobilization, and grassroots reformers in the labor, civil rights, feminist, and AIDS activist movements have concentrated more on immediate and incremental changes than on transforming the health care system itself. However, grassroots health care demands have also contained the seeds of a wider critique of the American health care system, leading some movements to adopt calls for universal coverage.